New Light on An Old Friend: Targeting PUMA in Radioprotection and Therapy of Cardiovascular and Neurodegenerative Diseases - Tichy, Ales; Marek, Jan; Havelek, Radim; Pejchal, Jaroslav; Seifrtova, Martina; Zarybnicka, Lenka; Filipova, Alzbeta; Rezacova, Martina; Sinkorova, Zuzana (Current drug targets, 2018)
This review summarizes recent progress in understanding the role of p53-upregulated mediator of apoptosis (PUMA) in molecular pathways with respect to its potential therapeutic applications. Particular emphasis is given to the PUMA´s role in ionizing radiation-induced signalling as radiotoxicity of normal tissue is mediated mostly via apoptosis. PUMA and its p53-dependent and p53- independent induction are described and potential use as a new target for the development of radioprotective agents is suggested. Further implications, including targeting PUMA to prevent and treat cardiovascular and neurodegenerative diseases, are also discussed together with an overview of other therapeutic applications. Finally, basic chemical structures for the development of novel PUMA modulators such as pifithrine derivatives, kinase inhibitors or modulators of Bcl-2 protein family are described.
Keywords: nádorový supresorový protein p53; Molecular Targeted Therapy; signální transdukce; DNA Damage; hearth; Radiation-Protective Agents; apoptóza; neuroprotektivní látky; tolerance záření; Protein Binding; Radiation Tolerance; small molecule inhibitor.; Neuroprotective Agents; Cardiovascular Agents; PUMA; radiační poranění; poškození DNA; Signal Transduction; Proto-Oncogene Proteins; Radiation Injuries; Tumor Suppressor Protein p53; radioprotection; Neoplasms; Cardiovascular Diseases; ionizing radiation; Apoptosis Regulatory Proteins; Humans; nádory; kardiovaskulární látky; vazba proteinů; protoonkogenní proteiny; cílená molekulární terapie; proteiny regulující apoptózu; neurodegenerativní nemoci; Neurodegenerative Diseases; kardiovaskulární nemoci; lidé; radioprotektivní látky; Apoptosis; brain